Pengaruh Psychological Capital terhadap Work Engagement pada Dosen - Zalfa Annisa Fitri; Hendro Prakoso; Vici Sofianna Putera (UNISBA Press, 2023)
The aim of this study to determine how much effect psychological capital on the work engagement of lecturers. The sample in this study amounted to 95 lecturers at the Islamic University of Bandung, Pasundan University, and the University of Indonesia Education. This study uses a psychological scale for psychological capital was measured using the Psychological Capital Questionnaire-24 (PCQ-24) by Fred Luthans, Bruce J. Avolio & James B. Avey (2007). Work engagement was measured using the Utrecht Work Engagement Scale–17 ( UWES-17) from Schaufeli & Bakker (2002), which has been adapted by Sutisna et al., (2020). The study's multiple regression method results show that psychological capital has an effect on work engagement by 44.6%, with the hope dimension having the most significant effect on work engagement. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh psychological capital terhadap work engagement dosen. Sampel dalam penelitian ini berjumlah subjek 95 dosen di Universitas Islam Bandung, Universitas Pasundan, dan Universitas Pendidikan Indonesia. Penelitian ini menggunakan skala psikologis untuk psychological capital menggunakan alat ukur Psychological Capital Questionaire-24 (PCQ-24) dari Fred Luthans, Bruce J. Avolio & James B. Avey (2007) dan alat ukur work engagement menggunakan Utrecht Work Engagement Scale– 17 (UWES-17) dari Schaufeli & Bakker (2002) yang telah diadaptasi oleh Sutisna et al., (2020). Hasil penelitian dengan menggunakan metode multiple regression menunjukkan bahwa psychological capital memberikan pengaruh pada terhadap work engagement sebesar 44.6%, dengan dimensi hope yang memberikan pengaruh paling besar terhadap work engagement.